Diversification, Branding and Performance of Professional Service Firms - Castaldi, Carolina; Giarratana, Marco (SAGE Publications Inc., 2018)
This article analyzes the effects of diversification and brand breadth on firm performance for professional service firms (PSFs). The research aim is two-fold. First,we test whether moving into products may put at risk the core resources that sustain PSFs’ competitive advantage. Second,we study which branding strategies best match their diversification attempts. Broad (narrow) brands characterize a branding strategy with scarce (plentiful) associations to specific product characteristics. We analyzed trademark portfolios of 47 U.S.-based management consulting firms in the 2000 to 2009 time period. Panel regression results suggest that (1) PSFs always benefit from diversification when they remain pure-service providers; (2) performance is positively related to a strategy of specialized narrow brands. © 2018,The Author(s) 2018.
Keywords: brand breadth; diversification; performance; professional service firms; 53 Ciencias Económicas::5311 Organización y dirección de empresas ::5311.02 Gestión financiera; ODS 9 - Industria, innovación e infraestructura